Upaya Peningkatan Kinerja Pengelolaan Keuangan Daerah melalui Kualitas Sumber Daya Manusia, Komitmen Organisasi, dan Budaya Organisasi - Mita Silfiani; Sigit Ary Wijayanto; Agus Khazin Fauzi (Strategic: Journal of Management Sciences, 2021)
This study aims to examine the influence of human resources, Organization commitment, and organization culture on financial management performance. The population of this study is all financial employees in the Mataram city regional revenue service. Data analysis is done by validity testing classical assumption test, and multiple linear regression analysis. These results indicate that variable quality of human resources had a significant positive effect on financial management performance in the Mataram city revenue service, organizational commitment variables had a significant positive effect on financial management performance, then organizational culture variables had a significant positive effect on financial management performance in Mataram city revenue. The research implications are explained further in the discussion